On the strong lacunary convergence and strong Cesáro summability of sequences of real-valued functions - Gökhan, A.; Güngör, M.; Bulut, Y. (Balkan Society of Geometers, 2006)
In this paper we introduce the concepts of the strong lacunary convergence and strong Cesáro summabilty of sequences of real-valued functions. We also give the relations between these convergences and pointwise convergence and pointwise statistical convergence. © Balkan Society of Geometers, Geometry Balkan Press 2006.
Keywords: Lacunary sequence; Pointwise statistical convergence; Strong lacunary convergence; Strongly Cesáro; Summable